"The Broken Wings" by Kahlil Gibran as an Inspiration in the Creation of Painting Artworks - Pratiwi, Retno Amalia; Hamzah, Hamzah; Aprisela, Jeki (V-art: Journal of Fine Art, 2025)
The Broken Wings is a novel by Kahlil Gibran that portrays a tragic love story rich in symbolism and emotional depth. This literary work, which stimulates strong visual imagination, inspired the creation of a series of surrealist-style paintings. The central themes—unfulfilled love and irreversible loss—are reinterpreted visually through impasto techniques using oil paint on canvas. The creative process began with a deep reflection on the novel’s emotional layers, followed by textual and visual research to develop symbolic compositions. A series of sketches explored various compositional possibilities before final realization on canvas. Each painting expresses aspects of the novel’s narrative through metaphorical imagery, colour symbolism, and textured surfaces. The outcome consists of five paintings, each representing key moments or emotional states drawn from the novel. These artworks were exhibited as part of a curated presentation, demonstrating how literature can be transformed into a compelling visual language. This creation contributes to the discourse of interdisciplinary art by bridging literary and visual narratives, offering new insights into emotional storytelling through painting.